Correlations between the severity of cardiovascular autonomic neuropathy and other complications in type 2 diabetes mellitus - Anca Motataianu; Zoltan Bajko; Smaranda Maier; Adina Stoian; Laura Barcutean; Rodica Balasa (Romanian Journal of Neurology, 2016)
Introduction. Cardiovascular Autonomic Neuropathy (CAN), also known as the “silent killer”, represents a serious complication of diabetes mellitus and is most of the times ignored. This is a highly topical issue, given the increased number of patients diagnosed with type 2 diabetes mellitus (T2DM). The purpose of this study was to determine the association between the severity of CAN and the severity of other microvascular complications, such as diabetic sensory-motor polyneuropathy (DSMP), diabetic retinopathy (DR) and macrovascular complications (carotid and peripheral vascular atherosclerosis) in patients with T2DM. Methods. A total of 149 patients with T2DM were assessed for CAN using the Ewing’s battery of cardiovascular autonomic function tests. The patients were evaluated for diabetic microvascular complications (DSMP, RD), respectively macrovascular complications (carotid atherosclerosis by intima media thickness and peripheral vascular atherosclerosis by ankle-brachial index). Results. Of the 45 patients with intermediate CAN, 35.55% were without DR, 51.11% had non-proliferative DR and 13.33% had proliferative DR. From the 13 patients with severe CAN, 76.92% had non-proliferative DR and 23.07% had proliferative DR. From the 56 patients with subclinical CAN, 26.7% had no DSMP, 48.2% had subclinical DSMP and 25% had clinical DSMP. Of the 45 patients with intermediate CAN, 11.2% had subclinical DSMP and 80% had clinical DSMP. Conclusion. In T2DM we demonstrated that an increase in the severity of cardiovascular autonomic injury is associated with an increase in the prevalence and severity of DSMP and DR, respectively carotid and peripheral atherosclerosis.